2020
DOI: 10.1038/s41598-020-74212-8
|View full text |Cite
|
Sign up to set email alerts
|

High sensitive label-free optical sensor based on Goos–Hänchen effect by the single chirped laser pulse

Abstract: We consider a four-level molecular system with two ground-state vibrational levels and two excited-state vibrational levels inside a constant cavity configuration. We discuss the reflected and transmitted Goos–Hänchen (GH) shifts of a positive and negative single-chirped laser pulse. The impacts of the laser field detuning, intensity of applied laser field, and appropriately tuning the chirp rate on GH shifts are then analyzed. It is also found that this sensor is very sensitive to the refractive index of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The optical behaviors have the potential to influence the characteristics of reflected light an In contrast to the refractive index, the concept of the complex refractive index encompasses fundamental optical parameters such as the refractive index and the absorption coefficient. It stands as a critical physical quantity for characterizing the optical properties of substances and holds significant relevance as an optical parameter for biological samples [31]. Notably, some prior studies, as documented in references [26,27], did not account for the impact of physical phenomena like absorption and attenuation within samples on the refractive index.…”
Section: Resultsmentioning
confidence: 99%
“…The optical behaviors have the potential to influence the characteristics of reflected light an In contrast to the refractive index, the concept of the complex refractive index encompasses fundamental optical parameters such as the refractive index and the absorption coefficient. It stands as a critical physical quantity for characterizing the optical properties of substances and holds significant relevance as an optical parameter for biological samples [31]. Notably, some prior studies, as documented in references [26,27], did not account for the impact of physical phenomena like absorption and attenuation within samples on the refractive index.…”
Section: Resultsmentioning
confidence: 99%
“…For example, biosensor applications include the design of a structure based on two-dimensional graphene and transition metal dichalcogenides to greatly enhance the GHS, improving the performance of plasmonic biosensors [5]. Additionally, high sensitive label-free optical sensors based on GHS effect have been studied by using a single chirped laser pulse [6]. It has also been shown that the sensitivity of bimetallic sensors based on the graphene-hexagonal boron nitride heterostructure can be enhanced by increasing the GHS in the infrared band [7].…”
Section: Introductionmentioning
confidence: 99%